Consumer's Surplus and the Compensating Variation - Henderson, A. (Review of Economic Studies, 1941)
Consumer's Surplus and the Compensating Variation A. Henderson A. Henderson Edinburgh Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 2, February 1941, Pages 117–121, https://doi.org/10.2307/2967468 Published: 01 February 1941